Opération McGill français - Warren, Jean-Philippe (Une douce anarchie. Les années 68 au Québec, 2008)
Book Authors: _:n56851
Keywords: Anglophones; Associations étudiantes; Francophones; Université McGill

Rocke Robertson: surgeon and shepherd of change - Pound, Richard W. (McGill-Queen's University Press, 2008)
Keywords: Anglophones; Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

Shared Values, Different Paths: First-Generation Iranian Men's and Women's Perceptions of the Cultural Production of an "Educated Person" - Sadeghi, Shiva (Université McGill, 2004)
Keywords: Iraniens; Étudiants

Self-Identification Processes and their Reflection in the Language of Fourth-Wave Emigrants in Montreal - Migdissova, Svetlana (Université McGill, 2003)
Keywords: Langue; Russes

Sebben che siamo donne (Although we are Women): a Comparative Study of Italian Immigrant Women in Post-War Canada and Australia - Iuliano, Susanna (Université McGill, 2001)
Understanding the lives of Italian women who migrated to Canada and Australia in the post-war period is the goal of this thesis. Although governments assigned women secondary roles as dependants and 'followers' in the migration process, I argue that Italian women were central, not marginal, to the migration and settlement experiences of Italian immigrants. By placing Italian women front and centre of this study, I contribute to a small but growing body of work that challenges the male-centred perspective of most literature on Italian-Canadian and Italian-Australian migration and ethnicity. This thesis is structured within a feminist framework and uses interdisciplinary methods to gather and interpret quantitative and qualitative information about the lives of Italian immigrant women in post-war Canada and Australia. Using government and church archives, personal interviews, ethnic newspapers, legal documents, marriage registers and participant observer fieldwork, I explore three major themes. Firstly, I examine Italian immigrant women's understanding of power relations within their homes and workplaces. Rather than cast women as either passive victims or all-conquering heroines, I present the complexity of the sources of power and weakness in immigrant women's lives. I argue that Italian immigrant women had to cope with exploitation and disadvantage because of their class, gender and ethnic status. However, they responded to these challenges with resistance and resilience, and were able to affect change and wield power within certain constraints. Secondly, I compare the experiences of migration and settlement for Italian immigrant women in Canada and Australia and show how women's experiences were united by common gender concerns. I found overwhelming similarities between the family lives and work experiences of Italian-Canadian and Italian-Australian immigrant women, and in the government policies and programs that attempted to direct their migration and settlement in the post-war period. Finally, I examine how Italian immigrant women helped to construct what it means to be 'Italian' in post-war Canada and Australia. I show how gender roles assigned to, and chosen by, Italian-Canadian and Italian-Australian women, served as boundary markers for ethnic difference. Perceived differences in attitudes towards waged work, mothering, family responsibilities and sexuality were used by Italian immigrant women to distinguish themselves as members of an ethnic collective. Lien avec Montréal - bien expliqué dans l'intro
Keywords: Femmes; Italiens

Sankofa: Recovering Montreal’s Heterogeneous Black Print Serials - Williams, Dorothy W. (Université McGill, 2006)
Keywords: Noirs

Représentations culturelles et identité d'immigrants adultes de Montréal apprenant le français - Amireault, Valérie (Université McGill, 2007)
Keywords: Langue

Using E-Government to Strengthen Montreal's Chinese Ethnic Economy - Han, Yang (Université McGill, 2006)
Keywords: Chinois; Commerce de détail; Internet

Britannique et Irlandaise: l'identité ethnique et démographique des Irlandais protestants et la formation d'une communauté à Montréal, 1834-1860 - Timbers, Wayne (Université McGill, 2001)
Keywords: Britanniques; Irlandais; Protestants

Collective Memory and Diasporic Articulations of Imagined Homes: Armenian Community Centres in Montreal - Manjikian, Lalai (Université McGill, 2005)
Keywords: Arméniens

"To Be Sold, a Negro Wench": Slave Ads of the Montreal Gazette, 1785-1805 - Extian-Babiuk, Tamara (Université McGill, 2006)
Keywords: Esclaves; Montreal Gazette; Noirs

Examining the Overrepresentation of Black Males in the Young Offender System - Johnson, Druscilla (Université McGill, 2000)
Keywords: Délinquance; Noirs

Not a Place, but a Culture: The Cultivation of Iranian Subjectivity in Montreal - Hashemzadeh, Kianoosh (Université McGill, 2009)
Keywords: Iraniens

Intégration et transnationalisme chez les Dominicains de Montréal - Dancause, Jacques-Luc (Université McGill, 2001)
Keywords: Caribéens

Cultural Sensitivity in the Context of Ethnic Polities: A Comparison of Two Families Service Agencies - Leung, Ho Hon (Université McGill, 2001)
Keywords: Chinois; Famille; Juifs

Political Economy, Transnationalism, and Identity: Students at the Montreal Hoshuko - Yoshida, Reiko (Université McGill, 2001)
Keywords: Japonais; Nationalisme

Reconstructing Tamil Masculinities: Kavati and Viratam among Sri Lankan Men in Montréal - Gross, Victoria (Université McGill, 2008)
Keywords: Sri Lankais

Young Second Language (L2) Learner's Meaning-Making: Consciousness, Collaboration, and Creativity (3Cs) - Kim, Mi Song (Université McGill, 2008)
Keywords: Coréens; Langue

Crisis? What Crisis?: Anglophone Musicmaking in Montreal - Stahl, Geoff (Université McGill, 2003)
Keywords: Anglophones; Musique

La letteratura dell'emigrazione italo-canadese di Montréal - Tedeschi, Antonio (Université McGill, 2000)
Keywords: Italiens

In the Shadow of the Mountain: A Historical Re-Evaluation of the 1988 Outremont Dispute - Herman, Dana (Université McGill, 2003)
Keywords: Juifs; Outremont

Italian Identity in Montreal: Issues of Intergenerational Ethnic Retention - De Martinis, Lucio (Université McGill, 2005)
Keywords: Italiens

In Search of Communal Identity: The Role of the Black Community in Identity Formation among Nigerian Youth - Ogbuagu, Buster C. (Université McGill, 2007)
Keywords: Nigériens; Noirs

Hearing (Unheard) Voices: Aboriginal Experiences of Mental Health Policy in Montreal - Macdonald, Mary Ellen (Université McGill, 2003)
Keywords: Autochtones

Growing Up in Three Languages: Triliteracy Practices of Chinese Immigrant Children in Quebec - Curdt-Christiansen, Xiao Lan (Université McGill, 2003)
Keywords: Chinois; Langue

The Emigration of Adam Smith's Ploughman: A Case Study of the Intellectual Culture of Scots Emigrants to Lower Canada, 1760-1850 - Gibson, Sarah Katherine (Université McGill, 2007)
Keywords: Écossais

Imperialist Intent - Colonial Response : The Art Collection and Cultural Milieu of Lord Strathcona in Nineteenth-Century Montreal - Pierce, Alexandria (Université McGill, 2002)
Keywords: Smith; Donald